(The issue of vomiting, epistaxis, reciting poetry, shaking hands with an infidel, touching a dog, one of them invalidates ablution or not?) Study and investigation (Journal of the College of Basic Education, 2023)
Summary of the research:This research came to study one of the symbols of the Akhbari school in the twelfth century AH, as it dealt with one of his jurisprudential writings. After relying on God and choosing research to be the subject of my thesis to obtain a master’s degree, I reviewed the catalogs of libraries that contain these valuables. So my share of the investigation was twenty issues, to participate in the revival of the Islamic heritage for the benefit of the people in general and the request for knowledge in particular, and here I will address the investigation of one of the manuscript issues, which is a jurisprudential issue in purity.Keywords: Samaheeji, ablution.